Cruises, crowds and fragile ecosystems: the delicate dance of Antarctic tourism by Peter Hannam - Nielsen, HE (Guardian News & Media Limited, 2023)
As the icy continent braces for a record summer, ecologists say more visitor caps and restrictions are needed to protect wildlife.